2016
DOI: 10.3390/ijms17071030
|View full text |Cite
|
Sign up to set email alerts
|

The Immunogenicity of Colorectal Cancer in Relation to Tumor Development and Treatment

Abstract: Although most cancer types have been viewed as immunologically silent until recently, it has become increasingly clear that the immune system plays key roles in the course of tumor development. Remarkable progress towards understanding cancer immunogenicity and tumor-immune system interactions has revealed important implications for the design of novel immune-based therapies. Natural immune responses, but also therapeutic interventions, can modulate the tumor phenotype due to selective outgrowth of resistant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 127 publications
(197 reference statements)
0
35
0
4
Order By: Relevance
“…With recent progress, it is evident that genetic alterations underlie the development of tumors and contribute to the formation of immunogenic tumor‐specific antigens, which allow the identification and elimination of CRC cells by the immune system. Tumor neoantigens have been defined as a novel class of tumor‐specific antigens derived from mutated proteins only in tumor cells . Rooney et al found that antitumor immune responses in CRC positively correlated with the expression of tumor neoantigens on the tumor cell surface.…”
Section: Therapeutic Implications Of Crc Immunogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…With recent progress, it is evident that genetic alterations underlie the development of tumors and contribute to the formation of immunogenic tumor‐specific antigens, which allow the identification and elimination of CRC cells by the immune system. Tumor neoantigens have been defined as a novel class of tumor‐specific antigens derived from mutated proteins only in tumor cells . Rooney et al found that antitumor immune responses in CRC positively correlated with the expression of tumor neoantigens on the tumor cell surface.…”
Section: Therapeutic Implications Of Crc Immunogenicitymentioning
confidence: 99%
“…Rooney et al found that antitumor immune responses in CRC positively correlated with the expression of tumor neoantigens on the tumor cell surface. Commonly expressed tumor‐associated antigens in CRC include mucin 1, carcinoembryonic antigen, HER2/neu, EGFR, epithelial cell adhesion molecule, telomerase, heparanase, and TP53 . Overexpression of TP53 is found in 50% of CRC tumors .…”
Section: Therapeutic Implications Of Crc Immunogenicitymentioning
confidence: 99%
“…Подавление активности Т-лимфоцитов наступает, когда экспрессированная ими молекула CTLA-4 взаимодействует с молекулой В7 на антигенпрезентирующей клетке. Другой способ дезактивации Т-лимфоцитов осуществляется при вза-имодействии экспрессированных ими молекул PD-1 с их лигандами PD-L1 или PD-L2 на антигенпрезен-тирующих клетках [35][36][37].…”
Section: Introductionunclassified
“…7 Colorectal КОЛОПРОКТОЛОГИЯ 4' 2017 О б з о р л и т е р а т у р ы система способна распознавать их и, соответственно, элиминировать из организма. Но при образовании опухолью новых вариантов белков, не узнаваемых иммунной системой, опухоль может избежать ее над-зора [37].…”
Section: Introductionunclassified
See 1 more Smart Citation